METODE BERMAIN PERAN TERHADAP KETERAMPILAN BERBICARA SISWA DI KELAS V PADA PEMBELAJARAN BAHASA INDONESIA - Uyun, Asral; Mulabbiyah; Akmaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The speaking skills of Year 5 pupils at MIN Lombok Timur are still relatively low, as evidenced by a lack of confidence, fluency, intonation and the ability to express opinions during the learning process. This study aims to determine the effect of the role-play method on pupils’ speaking skills in Indonesian language lessons in Year 5 at MIN Lombok Timur during the 2025/2026 academic year. This study employed a quantitative research design, specifically a quasi-experimental design. The results showed that the hypothesis test yielded a significance value of 0.003 < 0.05, meaning that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Consequently, it can be concluded that the role-play method has a significant effect on the speaking skills of students in Indonesian.